Effects of Ethanol on Sensory Inputs to the Medial Giant Interneurons of Crayfish - Swierzbinski, Matthew E.; Herberholz, Jens (Frontiers in Physiology, 2018)
Crayfish are capable of two rapid, escape reflexes that are mediated by two pairs of giant interneurons, the lateral giants (LG) and the medial giants (MG), which respond to threats presented to the abdomen or head and thorax, respectively. The LG has been the focus of study for many decades and the role of GABAergic inhibition on the escape circuit is well-described. More recently, we demonstrated that the LG circuit is sensitive to the acute effects of ethanol and this sensitivity is likely mediated by interactions between ethanol and the GABAergic system. The MG neurons, however, which receive multi-modal sensory inputs and are located in the brain, have been less studied despite their established importance during many naturally occurring behaviors. Using a combination of electrophysiological and neuropharmacological techniques, we report here that the MG neurons are sensitive to ethanol and experience an increase in amplitudes of postsynaptic potentials following ethanol exposure. Moreover, they are affected by GABAergic mechanisms: the facilitatory effect of acute EtOH can be suppressed by pretreatment with a GABA receptor agonist whereas the inhibitory effects resulting from a GABA agonist can be occluded by ethanol exposure. Together, our findings suggest intriguing neurocellular interactions between alcohol and the crayfish GABAergic system. These results enable further exploration of potentially conserved neurochemical mechanisms underlying the interactions between alcohol and neural circuitry that controls complex behaviors.